2008
DOI: 10.1255/ejms.927
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Tyrosine Nitration Sites in Human Endothelial Nitric Oxide Synthase by Liquid Chromatography-Mass Spectrometry

Abstract: The formation of nitric oxide (NO) in biological systems has led to the discovery of a number of post- translational protein modifications that can affect biological conditions such as vasodilation. Studies both from our laboratory and others have shown that beside its effect on cGMP generation from soluble guanylate cylcase, NO can produce protein modifications through both S-nitrosylation of cysteine residues. Previously, we have identified the potential S-nitrosylation sites on endothelial NO synthase (eNOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Among the proteins known to be nitration-inhibited are MnSOD and eNOS [53-55]. Our results show that nitration of both MnSOD (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Among the proteins known to be nitration-inhibited are MnSOD and eNOS [53-55]. Our results show that nitration of both MnSOD (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…This scavenging not only compromises the vasodilatory, antiproliferative, antithrombotic, and anti-inflammatory properties of NO, but also results in the formation of highly deleterious peroxynitrite that, in turn, induces nitration of cell proteins. Many proteins are known to be susceptible to nitration and in particular the nitration of MnSOD and eNOS inhibits their activity [53-55]. MnSOD is among the most important enzymes in the first line of oxidative stress defense, and its inhibition would inevitably exacerbate the severity of further oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the amount of peroxynitrite in the pulmonary vasculature might alter the number and location of the tyrosine residues nitrated, which could, in turn, determine whether eNOS is partially uncoupled or completely inhibited. For example, our recent study demonstrated that 19 of the 30 tyrosine residues found in eNOS could be nitrated (50). Interestingly, our data identified 4 such tyrosine residues in the region of eNOS responsible for the binding to HSP90 (13).…”
Section: Discussionmentioning
confidence: 55%
“…We have previously found both in vitro and in vivo that exogenous NO exposure causes an increase in peroxynitrite production and that increased eNOS nitration is involved in eNOS inhibition (60). Recently, using liquid chromatography/mass spectrometry, we elucidated the nitration sites on eNOS (64). In this study, we have identified four tyrosine residues that can be modified by nitration and are located in the region of eNOS responsible for the binding to heat shock protein 90 (HSP90).…”
Section: Discussionmentioning
confidence: 92%